Bacteriemia por Chryseobacterium indologenes em diabético em hemodiálise ambulatorial Bacteremia by Chryseobacterium indologenes in a diabetic patient undergoing ambulatory hemodialysis - Marcus Machado Ramos Souza de Souza; Cassiano Augusto Braga Silva; Edson Luiz Paschoalin; José Andrade Moura Júnior; Raphael Pereira Paschoalin; Ernesto Pereira de Oliveira (Sociedade Brasileira de Patologia Clínica, 2012)
Chryseobacterium indologenes é uma bactéria de baixa virulência, encontrada no meio ambiente, raramente associada às infecções não hospitalares. A maioria das infecções causadas por ela associa-se ao uso de dispositivos invasivos durante a permanência em hospital. O presente relato trata de paciente renal crônico, diabético, apresentando episódios de bacteriemia durante sessões de hemodiálise ambulatorial por meio de cateter permcath. Chryseobacterium indologenes is a low-virulent bacterium found in the environment, which is rarely associated with non-nosocomial infections. Most infections caused by this pathogen are associated with the use of invasive devices in hospitalized patients. This study reports the case of a diabetic patient with chronic renal disease presenting episodes of bacteremia undergoing ambulatory hemodialysis with permcath catheter.